Hypercrosslinked silole‐containing microporous organic polymers with N‐functionalized pore surfaces for gas storage and separation. Issue 8 (31st October 2017) - Shu, Ge; Zhang, Chong; Li, Yuda; Jiang, Jia‐Xing; Wang, Xunchang; Li, Hui; Wang, Feng
ABSTRACT: Novel hypercrosslinked microporous organic polymers (MOPs) derived from N‐functionalized siloles as basic building units have been designed and synthesized via Friedel–Crafts alkylation reaction. The resulting N‐functional silole‐containing polymer networks exhibit high thermal stabilities and moderate Brunauer–Emmett–Teller surface area ranging from 666 to 1137 m 2 g −1 . The incorporation of carbazole or triphenylamine moieties into the polymer skeleton increases the number of electron donating basic nitrogen sites in the porous frameworks. Thus, the corresponding polymer PDMCzS shows enhanced CO2 adsorption capacities of 3.23 mmol g −1 at 273 K and 1.13 bar, and higher CO2 /N2 selectivity (43.99) at 273 K than the analogous silole‐containing polymers P1–P3. These results demonstrated that the N‐functionalized silole‐containing polymer network is a very promising candidate for potential applications in post‐combustion CO2 capture and sequestration. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45907. Abstract :